2003
DOI: 10.1109/tasc.2003.813082
|View full text |Cite
|
Sign up to set email alerts
|

Irregular AC losses with long time constants in large cable-in-conduit conductors

Abstract: A large superconducting coil wound with Cable-in-Conduit (CIC) conductor causes both irregular AC losses that cannot be estimated from short conductor sample test results, and regular AC losses that are proportional to cable twisting pitch squared. We proposed a mechanism forming loops that generated the irregular losses. The CIC conductor is composed of several stages of sub-cables. If one strand on the surface of a sub-cable contacts another strand on the surface of the adjacent sub-cable, the two strands mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The averaged contact lengths in Type C and Type D conductors were larger than those of Type A and Type B. In the cross section of CIC conductors, large strand displacements from their original locations were observed at the rate of around 10% [3]. Assuming that irregular coupling loss with long time constant is caused by a long contact between strands and the long contact is generated by the large strand displacement, we can consider that the upper 10% of measured contact lengths are closely related to the 10% of large strand displacements and the irregular coupling loss.…”
Section: Contact Length Between Strandsmentioning
confidence: 84%
See 1 more Smart Citation
“…The averaged contact lengths in Type C and Type D conductors were larger than those of Type A and Type B. In the cross section of CIC conductors, large strand displacements from their original locations were observed at the rate of around 10% [3]. Assuming that irregular coupling loss with long time constant is caused by a long contact between strands and the long contact is generated by the large strand displacement, we can consider that the upper 10% of measured contact lengths are closely related to the 10% of large strand displacements and the irregular coupling loss.…”
Section: Contact Length Between Strandsmentioning
confidence: 84%
“…To clarify the mechanism of irregular coupling losses, we have investigated the strand locations within a cross-section of CIC conductors and found that some strands widely displaced from their original positions [3]. Such displacement causes the reduction of contact resistance between strands, because contact area between strands becomes much larger than that of theory.…”
Section: Introductionmentioning
confidence: 99%
“…In large superconducting coils wound with CIC conductors, there are two types of coupling currents. One is the 'regular' coupling current which can be estimated by the cabling pattern of a CIC conductor [13,14]. The other is the 'irregular' coupling current which is an unexpected phenomenon from the conductor design.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous works proved that the characteristic length of long current loop estimated from the magnetic field signals which were measured by Hall probes was near the LCM (Least Common Multiplier) of all staged cable pitches [3] and the contact conditions of two strands would be partly line contact due to widely displacement of triplets which are different from expected point contact conditions Manuscript [4]. Although these researches can explain the measured time constant of the loss, there is no estimation of the time constant based on actual contact conditions of strands in CICC.…”
Section: Introductionmentioning
confidence: 96%